Characterization of an Isogenic Mutant of Streptococcus pyogenes Manfredo Lacking the Ability To Make Streptococcal Acid Glycoprotein - Degnan, B. A. (American Society for Microbiology, 2000)
An isogenic mutant of Streptococcus pyogenes Manfredo that lacks the ability to make streptococcal acid glycoprotein (SAGP) has been constructed by inserting a deletion in the sagp gene using the method of allelic exchange. An assay of cell extracts (CE) prepared from the wild-type and mutant Manfredo strains for the enzyme arginine deiminase (AD) showed that significant activity was present in wild-type CE but none could be detected in mutant CE. These findings confirm our earlier conclusion that SAGP has AD activity (B. A. Degnan, J. M. Palmer, T. Robson, C. E. D. Jones, M. Fischer, M. Glanville, G. D. Mellor, A. G. Diamond, M. A. Kehoe, and J. A. Goodacre, Infect. Immun. 66:3050–3058, 1998). Wild-type CE but not mutant CE potently inhibited human peripheral blood mononuclear cell proliferation in response to phytohemagglutinin, and this inhibition was overcome by the addition of l-arginine to proliferation assay mixtures. Invasion assays showed that the isogenic mutant organisms lacking SAGP, and thus AD activity, were between three and five times less able to enter epithelial cells (Hep-2C and A549) than were the wild-type streptococci. Both wild-type and mutant S. pyogenes bacteria were extremely sensitive to low pH. However, l-arginine (1 mM or above) significantly increased the viability of the wild type but not the isogenic mutant organisms under acidic conditions. The difference in acid susceptibility between wild-type and mutant bacteria may explain the reduced capacity of the isogenic mutant bacteria to invade and survive intracellularly.